Intriguing Carbon Flake Formation during Microwave‐Assisted Hydrothermal Carbonization of Sodium Lignosulfonate (Global Challenges 8/2020). Issue 8 (6th August 2020) - Melilli, Giuseppe; Adolfsson, Karin H.; Impagnatiello, Andrea; Rizza, Giancarlo; Hakkarainen, Minna
Abstract : In article number 1900111 Minna Hakkarainen and co‐workers reveal formation of elongated carbon flakes after microwave‐assisted hydrothermal carbonization of sodium lignosulfonate. The formed carbon flakes are shown to consist mainly of nanographitic domains with a high degree of defects such as oxygenated functional groups. Furthermore, new insights into the formation mechanisms are uncovered. Carbon flakes are anticipated to be highly interesting products for variety of material applications.